Impact Of Performance Of Coir Industry On Indian Economy - P NAVITHA; M JEGADEESHWARAN (Perkumpulan Dosen Muslim Indonesia, 2024)
The focus of the study is to analyse performance of the coir industry in India and its impact on the economy during the period 2011-12 to 2020-21. The study is based on Secondary data. For the analysis of data tools like descriptive statistics and regression is used in the study. The study shows that coir fibre and coir yarn is produced more in India and the production of different coir items grow at and equal rate which indicates the progress and development of the industry. Coir fibre, Coir pith and tufted mat are the major coir items exported from the country. Coir exports is growing year after year and is significantly impacting the economic development of the country.